Discrepant effects of mexiletine on cycle length of ventricular tachycardia and on the effective refractory period in the area of slow conduction. Issue 3 (March 1996) - Aizawa, Y.; Chinushi, M.; Kitazawa, H.; Washizuka, T.; Abe, A.; Shibata, A.; Kodama, I.
Abstract : OBJECTIVE: Monomorphic sustained ventricular tachycardia (VT) can often be entrained and interrupted at a critical paced cycle length. The aim was to evaluate a possible determinant of this phenomenon by observing the action of mexiletine on the critical paced cycle length and other variables. METHODS: Nine consecutive patients with symptomatic VT were studied. After induction of VT, the area of slow conduction was mapped as the earliest site of the activation or the site with mid-diastolic potential during the tachycardia. Rapid pacing was performed at a site distant from the tachycardia circuit to entrain the tachycardia, starting at a cycle length 10-20 ms shorter than the VT cycle length, and repeated after a decrement of the cycle length in steps of 10 ms to obtain the longest paced cycle length that interrupted the tachycardia: the block cycle length. The effective refractory period (ERP) was measured at the pacing site at which the myocardium was presumed to be normal and also in the area of slow conduction. The effects of mexiletine on the cycle length of VT, the block cycle length, and the ERP at two sites were obtained before and after mexiletine administration. The relation between the cycle length of VT and block cycle length and their changes were also analysed. RESULTS: 11 VTs with the same morphology were induced before and after mexiletine administration. The VT cycle length was prolonged by mexiletine from 309 (SD 53) to 361 (47) ms, and it was interrupted at block cycle lengths of 247 (37) and 307 (41) ms, respectively, the changes being 18 (12)% and 23 (8)% (both P < 0.001). All VTs were entrained, and during pacing at the block cycle length there was abrupt loss of fusion and change in the presystolic electrogram, always associated with interruption of VT on cessation of rapid pacing. A good correlation was observed between the VT cycle length and the block cycle length (r = 0.77 to 0.80). The ERP at the pacing site (normal myocardium) and in the area of slow conduction showed no significant change: 241 (21) v 240 (22) ms and 262 (9) v 252 (9) ms, respectively. The block cycle length was longer than the ERP after mexiletine administration: 362 (55) v 252 (9) ms (P < 0.02). CONCLUSIONS: Mexiletine prolonged the cycle length of VT and the VT-interrupting critical cycle length but not the ERP. The prolongation of the VT cycle length and the block cycle length by mexiletine seemed to be unrelated to the action potential duration, but related to depressed intercellular conduction.